Analisis Yuridis terhadap Perkawinan Perempuan Muallaf dengan Wali Nikah Tokoh Agama: (Studi atas Penetapan Nomor 20/Pdt.P/2012/PA.Smi dan Penetapan Nomor 6/Pdt.P/2013/PA.Sgr) - Makbul Bakari; Rizal Darwis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2019)
This research discusses to study and analyze the legal considerations of the Panel of Judges' judgments in Stipulation Number 20/Pdt.P/2012/PA.Smi and Stipulation Number 6/Pdt.P/2013/PA.Sgr. about itsbāt nikah in marriage of muallaf women with marriage guardians of religious leaders, then comparing the results of the two determinations. This research is a type of library research that acts descriptive-analytical-comparative. The choices used are juridical-normative and syara. The results of this study indicate that the contextual interpretation of the legal text more fulfills a sense of justice in favor of textual interpretation. Stipulation Number 6/Pdt.P/2013/PA.Sgr. which departs from contextual interpretation by considering socio-cultural and legal awareness of the community and contra legem by way of questioning the meaning (supported legal interpretation) of terminology). Honower Stipulation Number 20/Pdt.P/ 2012/PA.Smi which starts from textual-legalistic interpretation cannot fulfill the sense of justice of the community, but can only fulfill procedural demands.